Warming Tropical Indian Ocean Wets the Tibetan Plateau - Aoqi Zhou; Chaoxia Yuan; Jing‐Jia Luo; Toshio Yamagata (Geophysical Research Letters)
Abstract Accurate detection and attribution of past climate change are crucial for projecting future climate change and formulating proper policies. In this study, we show that the warming of the tropical Indian Ocean contributes to the observed wetting trend in the Tibetan plateau. The warming tropical Indian Ocean can lead to more precipitation around the Arabian Sea. The associated diabatic heating triggers the cyclonic atmospheric response in the lower troposphere over the Arabian Sea and eastern Africa. It also causes the enhancement and westward extension of the western North Pacific subtropical high. The in‐between airflow transports more moisture northward to the plateau, leading to the increased precipitation over the plateau. These large‐scale circulation patterns can be detected from the long‐term trends based on the observations and the large‐ensemble historical simulations. They can also be simulated by an atmospheric general circulation model forced by the observed warming merely in the tropical Indian Ocean.